A comparative study of BRTV and NTA Maiduguri regarding their compliance with Nigeria Broadcasting Code on religious programming - Ibrahim Uba Yusuf; Musa Usman; Adamkolo Mohammed Ibrahim (Universitas Negeri Yogyakarta, 2020)
The regulation of broadcast religious programming is a critical challenge the National Broadcasting Commission (NBC) is facing in Nigeria. In Maiduguri, the capital of the north-eastern Nigerian state of Borno where religion forms a core part of the people’s culture, a great deal of Borno Radio Television (BRTV) and Nigerian Television Authority Maiduguri’s (NTA Maiduguri) airtime is allocated to Islamic preaching during the Muslim’s annual Ramadan fasting. However, there is a dearth of research on whether the airtime those broadcast stations allocate to Islamic programming complies with the NBC code on religious programming. This research gap formed the main research question of this study which was conducted during the second quarter of 2019. Primary data were collected using key informant interviews with five personnel from the two broadcast stations and the Maiduguri office of NBC, while secondary data were obtained through the review of official documents. Key findings showed that the airtime allocated to religious programmes exceeded the 10% NBC limit, BRTV allocated more airtime to religious programmes than NTA Maiduguri and Islamic programmes were allocated more airtime than programmes of other religions. Recommendations on how to improve compliance to NBC’s regulations were offered at the end.Peraturan program siaran keagamaan merupakan tantangan bagi National Broadcasting Commission (NBC)/Komisi Penyiaran Nasional di Nigeria. Maiduguri, ibukota Negara bagian Borno, Nigeria Timur Laut di mana agama merupakan bagian inti dari budaya masyarakat, banyak Radio Televisi Borno (BRTV) dan Otoritas Televisi Nigeria Maiduguri (NTA Maiduguri) mengalokasikan jam tayang untuk khotbah Islam selama Ramadhan. Namun, ada kelangkaan penelitian tentang apakah jam tayang yang disiarkan oleh stasiun-stasiun siaran itu untuk program Islami. Kesenjangan penelitian ini membentuk pertanyaan penelitian utama yang dilakukan selama kuartal kedua 2019. Data penelitian ini dikumpulkan menggunakan wawancara informan kunci dengan lima personel dari keduanya stasiun siaran dan kantor Maiduguri NBC, sementara data sekunder diperoleh melalui telaah dokumen resmi. Temuan penelitian ini menunjukkan bahwa “airtime” (jam tayang) dialokasikan untuk program keagamaan yang melebihi batas 10% NBC, BRTV mengalokasikan lebih banyak “airtime” ke program keagamaan dari NTA Maiduguri dan program Islam dialokasikan lebih banyak “airtime” daripada program agama lain. Implikasi dari penelitian ini adalah perlunya kepatuhan terhadap peraturan NBC.